Effect of temperature on corrosion behavior of E690 steel in 3.5 wt.% NaCl solution. (22nd January 2021) - Yan, Qi; Yin, Qun; Cui, Jie; Wang, Xinyi; Qiao, Yanxin; Zhou, Huiling
Abstract: The corrosion behavior of E690 steel in 3.5 wt.% NaCl solution at temperatures from 20 °C to 60 °C was investigated using electrochemical test. The corrosion morphology was characterized using SEM and AFM, and the corrosion layer was characterized using EDS, Raman spectroscopy and XPS. The results showed that the corrosion rate of E690 steel improves with the increase in temperature. The corrosion layers of E690 steel are mainly composed of α -Fe2 O3, α -FeOOH and γ -FeOOH. With the elevated temperature, the content of α -FeOOH in corrosion layers increases, while the content of α -Fe2 O3 and γ -FeOOH decreases. The corrosion mechanisms were briefly discussed.